Candida albicans targets that potentially synergize with fluconazole. (4th May 2021) - Lu, Hui; Shrivastava, Manjari; Whiteway, Malcolm; Jiang, Yuanying
Abstract: Fluconazole has characteristics that make it widely used in the clinical treatment of C. albicans infections. However, fluconazole has only a fungistatic activity in C. albicans, therefore, in the long-term treatment of C. albicans infection with fluconazole, C. albicans has the potential to acquire fluconazole resistance. A promising approach to increase fluconazole's efficacy is identifying potential targets of drugs that can enhance the antifungal effect of fluconazole, or even make the drug fungicidal. In this review, we systematically provide a global overview of potential targets of drugs synergistic with fluconazole in C. albicans, identify new avenues for research on fluconazole potentiation, and highlight the promise of combinatorial strategies with fluconazole in combatting C. albicans infections.